2015
DOI: 10.1039/c4ra13754j
|View full text |Cite
|
Sign up to set email alerts
|

Removal of NO with silicene: a DFT investigation

Abstract: NO can be adsorbed onto silicene and then reduced into N2via a dimer mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…[164][165][166] Two dissociation mechanisms for NO have been proposed. 167 One is a direct breaking of the N-O bond with an energy barrier of 0.47 eV and a subsequent formation of Si-O and Si-N bonds. The other is the formation of a (NO) 2 dimer and subsequent decomposition into N 2 and two O atoms bonded with Si (energy barrier of 0.45 eV).…”
Section: Gas Adsorbentmentioning
confidence: 99%
“…[164][165][166] Two dissociation mechanisms for NO have been proposed. 167 One is a direct breaking of the N-O bond with an energy barrier of 0.47 eV and a subsequent formation of Si-O and Si-N bonds. The other is the formation of a (NO) 2 dimer and subsequent decomposition into N 2 and two O atoms bonded with Si (energy barrier of 0.45 eV).…”
Section: Gas Adsorbentmentioning
confidence: 99%
“…14−16 Remarkably, the binding energies of NO 2 , O 2 , and SO 2 on silicene are greater than 1 eV. 14,15,17 In some extent, it can be explained from the strength of formed π-orbital network of these two materials. In silicene (graphene), the π bond originates from the overlapping of 3p z (2p z ) electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent studies indicate that silicene possesses higher chemical reactivity to foreign atoms and molecules. For example, the metal atoms were reported to have stronger binding strength on silicene. In particular, the binding energy of Au atom is about 23 times greater than that on graphene. , Some common gas molecules, like NH 3 , NO, NO 2 , SO 2 , and O 2 were chemically inert to graphene, but all of them tend to chemisorption on silicene. Remarkably, the binding energies of NO 2 , O 2 , and SO 2 on silicene are greater than 1 eV. ,, In some extent, it can be explained from the strength of formed π-orbital network of these two materials. In silicene (graphene), the π bond originates from the overlapping of 3 p z (2 p z ) electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al revealed the potential of silicene in NO removal utilizing DFT calculations. [ 53 ] Two mechanisms for NO reduction on silicene were provided: a direct dissociation mechanism and a dimer mechanism. The former mechanism was characterized as the direct breaking of the NO bond.…”
Section: Catalytic Applications Of 2d Simentioning
confidence: 99%
“…The latter was identified to undergo a (NO) 2 dimer formation on silicene, which then decomposed into N 2 O + O ad or N 2 + 2O ad . [ 53 ] Itahara et al were the first to demonstrate the application of Si‐based nanomaterials for photocatalytic decomposition of nitrogen monoxiede (NO). [ 54 ] The synthesized nanocomposites composed of Si nanoflakes and metallic particles showed a wide light absorption range spanning 200–2000 nm ( Figure a).…”
Section: Catalytic Applications Of 2d Simentioning
confidence: 99%